PENEMUAN HUKUM HAKIM PENGADILAN PAJAK DALAM MEMUTUSKAN PBB HUTAN RESTORASI EKOSISTEM - Agus Suharsono; Aniek Juliarini (Puslatbang KHAN, 2020)
The Land and Building Tax of the Forestry sector managed by the DGT is an objective tax whose tax depends on the value of the object. The number of objections to land and building tax disputes in 2017 was 384 or 4% of all objections. Decision of Tax Court Number PUT-107539.18 / 2015 / PP / M.IVB related to the stipulation of Land and Building Tax on Land and Building Tax objects in the form of ecosystem restoration forest. This is interesting to analyze because the main issue of the calculation of the sale value of forest tax objects has an ecosystem restoration function that does not yet have a specific regulation. The method used is normative juridical research with approaches: law, concept, case, and analysis. The research data in the form of primary legal materials are all written regulations and decisions of the Tax Court, secondary legal materials in the form of books, articles, and legal dictionaries. Data is collected by literature study which is done by searching, researching, studying, recording, and interpreting by polyiangulation. The collected data is analyzed qualitatively by recording, studying, and interpreting and then explaining descriptively. The results of the study revealed that the Tax Court Judge in deciding the Land and Building Tax dispute over an object in the form of an ecosystem restoration forest was not bound by written regulations but also considered the judge's beliefs. In addition, it is known that there are no specific regulations governing the valuation of land and building tax objects on forests that have an ecosystem restoration function.